Relationship of observation depth and time against Perna viridis spawn in coastal waters of Waiheru Village, Inner Ambon Bay - Rettob, Mujahiddin Permata Roman; Eddy, La; Suriani, Sanita (Generasi Biologi Indonesia, 2024)
The adhesion of green mussel spit is highly correlated with depth. This study aims to establish the correlation between the depth and duration of observation with the abundance of green mussel spat (Perna viridis) in the coastal waters of Waiheru Village, located in Inner Ambon Bay. This study was undertaken utilising three floating net cages (KJA) possessed by local fishermen. The KJA utilised in this investigation had dimensions of 2.0 x 2.5 metres. Each KJA is equipped with 4 threads of hanger rope, resulting in a total of 12 hangers. Each rope hanger is positioned at specific depths, specifically at depths of 3, 6, and 9 metres. The net is 40 cm by 40 cm. Observations were conducted on days 2, 4, 6, 8, 10, 12, and 14 after the nets were strung. The findings indicated that the depth and duration of observation significantly influenced the quantity of green mussel spat. Specifically, more spat was observed compared to other days, suggesting a stronger attachment at that depth and observation period. Nevertheless, on the 10th day of observation, there was a surge in the quantity of green mussel spit.